Successful video-assisted thoracoscopic surgery in prone position in patients with esophageal cancer and aberrant right subclavian artery: report of three cases - Koji Shindo; Eishi Nagai; Toshinaga Nabae; Toru Eguchi; Taiki Moriyama; Kenoki Ohuchida; Tatsuya Manabe; Takao Ohtsuka; Yoshinao Oda; Makoto Hashizume; Masafumi Nakamura (Surgical Case Reports)
Abstract Background An aberrant right subclavian artery (ARSA) with an associated nonrecurrent right inferior laryngeal nerve (NRILN) is a relatively rare anomaly that occurs at a frequency of 0.3 to 2.0% of the general population. NRILN has been mainly documented in the head and neck region; it has been rarely described in patients with esophageal cancer, especially those undergoing thoracoscopic surgery. Video-assisted thoracoscopic surgery for esophageal cancer (VATS-E) is becoming more widespread as a reliable minimally invasive surgical procedure associated with reduced perioperative complications. Case presentation Herein, we report three cases of esophageal cancer with ARSA and NRILN which underwent successful VATS-E. Case 1, a 53-year-old male who had early stage esophageal cancer was performed VATS-E. Upper gastrointestinal (GI) series showed “Bayonet sign” (T1aN0M0, pStageIA in UICC). Case 2, a 75-year-old male who had advanced esophageal cancer was performed neoadjuvant chemotherapy and following VATS-E. This case had right thoracic duct and “Bayonet sign” on upper GI series (T1bN2M0, pStage IIIA in UICC). Case3, a 72-year-old male who had advanced esophageal cancer was performed neoadjuvant chemotherapy and following VATS-E (T3N2M0, pStageIIIB in UICC). All of these three cases were performed VATS-E and discharged without any complication. Conclusion VATS-E in the prone position is a feasible procedure that can reduce the risk of complications with an enlarged and clear view, and knowledge of this type of anomaly is very important for surgeons who perform esophagectomy.